Textbook Development Process in Andhra Pradesh - Reddy, N. Upender (Voices of Teachers and Teacher Educators, 2018)
This paper is about the effort of the State of undivided Andhra Pradesh to develop a curriculum framework document that would be in line with the National Curriculum Framework-2005 along with the position papers of the National Focus Groups developed during NCF-2005 exercise. The State based its efforts towards better syllabi and textbooks along with improved classrooms on the substantial work done earlier on its teacher capacity building and school support systems. The NCF-2005 and the position papers attached with it for the first time laid out in so much detail what was expected and needed from all aspects of the system and spelt out the directions and the focus areas. This encouraged us to use it as an opportunity to analyse what we had done in the light of our needs and situation in the State. We then worked on those ideas with a big team and drew upon our experience and knowledge to make the State Curriculum Framework, position papers and the syllabus. This exercise was followed by textbook writing. The effort to transform educational process was spread over many years and involved a committed amd dedicated effort of the state team with the support of extended team.